Long-Term Results of Combined Tunica Albuginea Plication and Penile Prosthesis Implantation for Severe Penile Curvature and Erectile Dysfunction - Luigi Cormio; Paolo Massenio; Giuseppe Di Fino; Giuseppe Lucarelli; Vito Mancini; Giuseppe Liuzzi; Giuseppe Carrieri (Case Reports in Urology)
Penile prosthesis implantation is the recommended treatment in patients with penile curvature and severe erectile dysfunction (ED) not responding to pharmacotherapy. Most patients with mild-to-moderate curvature can expect cylinder insertion to correct both ED and penile curvature. In patients with severe curvature and in those with persistent curvature after corporeal dilation and prosthesis placement, intraoperative penile “modelling” over the inflated prosthesis has been introduced as an effective treatment. We report for the first time the long-term results of a patient treated with combined penile plication and placement of an inflatable penile prosthesis.